Foramen Magnum Meningioma Presenting with Cough Syncope (Case Report and Review of the Literature) - Kaplan, Metin; Hepgunsel, Omer Batu; Kok, Selman; Gonen, Murat (Georg Thieme Verlag Kg, 2018)
Foramen magnum meningiomas cause different symptoms based on the size and the location of the tumor. They often present with involvement of the long tracts and of the lower cranial nerves. Ataxia and occipitocervical headache are other common symptoms. In the present study, we report a case of foramen magnum meningioma presenting with cough syncope. A mass lesion located anterolateral to the foramen magnum was detected in a 38-year-old man during amagnetic resonance imaging (MRI) exam; the lesion extended from the inferior clivus to the level of the C2 vertebra. The neural axis has pushed towards posterior and contralateral side by the mass. We think that syncope occurred due to the encasement of the vertebral arteries by the tumor in addition to the compression of the neural axis. The posterolateral approach without condylar resection provides a safe surgical plane for total excision of these tumors. In our case, the tumor was totally removed and the syncope episodes were resolved.
Keywords: far lateral approach; foramen magnum meningioma; syncope